DEVELOPMENT OF TRANSPORT AND TRANSPORT SYSTEMS - Кравченко, Олександра; Боровик, Світлана; Стеба, Анастасія; Шибаєв, Олександр (SWorldJournal, 2025)
The article reviews the global timber market, identifies leading exporters and importers. The current state of Ukraine’s forestry complex is described. Russia’s full-scale invasion of Ukraine in February 2022 and missile attacks led to a significant reduc